Bioefficacy of Plant Extracts on Collar Rot Disease (Sclerotium rolfsii Sacc.) of Soybean - Borah, Munmi; Gogoi, Sukanya (International Journal of Economic Plants, 2020)
Among different production constraints in soybean cultivation, the most serious being is diseases. In Assam and other North Eastern states, collar rot caused by Sclerotium rolfsii Sacc. has been found to be a major disease causing plant death and low productivity as rainfall has played a significant role in the establishment of progression of collar rot in soybean. Therefore, the study was undertaken to evaluate the bioefficacy of some commonly available plant extracts against Sclerotium rolfsii Sacc. The aqueous plant extracts of commonly available six plant species were evaluated in vitro by poisoned food technique against their inhibitory effect on the mycelial growth of Sclerotium rolfsii Sacc. Allium sativum was found to be most effective with growth inhibition of 89.77% followed by Chromolaena odorata (86.00%), Allamanda cathertica (83.66%), Laurus nobilis (72.11%), Ageratum conyzoides (54.88%) and Aegle marmelos (50.66%).